A gene-protein assay for human epidermal growth factor receptor 2 (HER2): brightfield tricolor visualization of HER2 protein, the HER2 gene, and chromosome 17 centromere (CEN17) in formalin-fixed, paraffin-embedded breast cancer tissue sections - Nitta Hiroaki; Kelly Brian D; Padilla Mary; Wick Nikolaus; Brunhoeber Patrick; Bai Isaac; Singh Shalini; Ranger-Moore Jim; Bieniarz Chris; Tsuda Hitoshi; Grogan Thomas M (BMC, 2012)
Abstract Background The eligibility of breast cancer patients for human epidermal growth factor receptor 2 (HER2)-directed therapies is determined by the HER2 gene amplification and/or HER2 protein overexpression status of the breast tumor as determined by in situ hybridization (ISH) or immunohistochemistry (IHC), respectively. Our objective was to combine the US Food and Drug Administration (FDA)-approved HER2 & chromosome 17 centromere (CEN17) brightfield ISH (BISH) and HER2 IHC assays into a single automated HER2 gene-protein assay allowing simultaneous detection of all three targets in a single tissue section. Methods The HER2 gene-protein assay was optimized using formalin-fixed, paraffin-embedded (FFPE) samples of the xenograft tumors MCF7 [HER2 negative (non-amplified gene, protein negative)] and Calu-3 [HER2 positive (amplified gene, protein positive)]. HER2 IHC was performed using a rabbit monoclonal anti-HER2 antibody (clone 4B5) and a conventional 3,3'-diaminobenzidine IHC detection. The HER2 & CEN17 BISH signals were visualized using horseradish peroxidase-based silver and alkaline phosphatase-based red detection systems, respectively with a cocktail of 2,4-dinitrophenyl-labeled HER2 and digoxigenin-labeled CEN17 probes. The performance of the gene-protein assay on tissue microarray slides containing 189 randomly selected FFPE clinical breast cancer tissue cores was compared to that of the separate HER2 IHC and HER2 & CEN17 BISH assays. Results HER2 protein detection was optimal when the HER2 IHC protocol was used before (rather than after) the BISH protocol. The sequential use of HER2 IHC and HER2 & CEN17 BISH detection steps on FFPE xenograft tumor sections appropriately co-localized the HER2 protein, HER2 gene, and CEN17 signals after mitigating the silver background staining by using a naphthol phosphate-containing hybridization buffer for the hybridization step. The HER2 protein and HER2 gene status obtained using the multiplex HER2 gene-protein assay demonstrated high concordance with those obtained using the separate HER2 IHC and HER2 & CEN17 BISH assays, respectively. Conclusions We have developed a protocol that allows simultaneous visualization of the HER2 IHC and HER2 & CEN17 BISH targets. This automated protocol facilitated the determination of HER2 protein and HER2 gene status in randomly selected breast cancer samples, particularly in cases that were equivocal or exhibited tumor heterogeneity. The HER2 gene-protein assay produced results virtually equivalent to those of the single FDA-approved HER2 IHC and HER2 & CEN17 BISH assays. Virtual slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2041964038705297